Sloshing Displacement Measurements Based on Morphological Image Analysis - YAZICI, GÖKHAN; SAATÇI, ERTUĞRUL (My University, 2018)
Sloshing of the contained liquid is an important issue, which needs to be dealt with in the design of moving liquid storage tanks, such as fuel tanks subjected to earthquakes. Numerical methods such as the finite element method or smoothed particle hydrodynamics are commonly used to analyze the sloshing response of liquids in the design of liquid storage containers. The analysis results obtained from numerical methods are usually validated through the comparison of free surface displacements obtained from laboratory tests conducted on scaled tank models. However, the equipment required for measurement can be quite costly and the setup of the measurement system for moving containers can be a tedious process. In order to simplify the measurement setup and reduce the associated cost, we propose a measurement system based on morphological image analysis using a stationary HD camera. In order to verify the validity of the proposed method a shaking table test was conducted on a transparent prismatic liquid tank subjected to a simulated earthquake base motion. The liquid tank was filled with colored water to facilitate image analysis. The video record of the experiment was processed by the proposed algorithm implemented in the MATLAB environment to measure the free surface displacements on the right wall of the tank. The free surface displacements obtained from the video record by automated image analysis were congruent with the manual measurements conducted on the individual video frames.